Size Matters: Ryanodine Receptor Cluster Size Affects Arrhythmogenic Sarcoplasmic Reticulum Calcium Release. Issue 13 (3rd July 2018) - Galice, Samuel; Xie, Yuanfang; Yang, Yi; Sato, Daisuke; Bers, Donald M.
Abstract : Background: Ryanodine receptors (RyR) mediate sarcoplasmic reticulum calcium (Ca 2+ ) release and influence myocyte Ca 2+ homeostasis and arrhythmias. In cardiac myocytes, RyRs are found in clusters of various sizes and shapes, and RyR cluster size may critically influence normal and arrhythmogenic Ca 2+ spark and wave formation. However, the actual RyR cluster sizes at specific Ca 2+ spark sites have never been measured in the physiological setting. Methods and Results: Here we measured RyR cluster size and Ca 2+ sparks simultaneously to assess how RyR cluster size influences Ca 2+ sparks and sarcoplasmic reticulum Ca 2+ leak. For small RyR cluster sizes (<50), Ca 2+ spark frequency is very low but then increases dramatically at larger cluster sizes. In contrast, Ca 2+ spark amplitude is nearly maximal even at relatively small RyR cluster size (≈10) and changes little at larger cluster size. These properties agreed with computational simulations of RyR gating within clusters. Conclusions: Our study explains how this combination of properties may limit arrhythmogenic Ca 2+ sparks and wave propagation (at many junctions) while preserving the efficacy and spatial synchronization of Ca 2+ ‐induced Ca 2+ ‐release during normal excitation‐contraction coupling. However, variations in RyR cluster size among individual junctions and RyR sensitivity could exacerbate heterogeneity of local sarcoplasmic reticulum Ca 2+ release and arrhythmogenesis under pathological conditions.